Influence of SARS-COV-2 Infection on Cytokine Production by Mitogen-Stimulated Peripheral Blood Mononuclear Cells and Neutrophils in COVID-19 Intensive Care Unit Patients - Sahar Essa; Mohammed Shamsah; Abdalaziz H. Alsarraf; Ali Esmaeil; Ahmed Al-Shammasi; Raj Raghupathy (Microorganisms, 2022)
We sought to investigate the influence of SARS-CoV-2 infection on the cytokine profiles of peripheral blood mononuclear cells (PBMCs) and neutrophils from coronavirus disease 2019 (COVID-19) intensive care unit (ICU) patients. Neutrophils and PBMCs were separated and stimulated with the mitogen phytohemagglutinin. Culture supernatants of mitogen-stimulated PBMCs and neutrophils from 88 COVID-19 ICU patients and 88 healthy controls were evaluated for levels of granulocyte-macrophage colony-stimulating factor (GM-CSF), interferon (IFN)-α, IFN-γ, interleukin (IL)-2, -4, -5, -6, -9, -10, -12, -17A, and tumor necrosis factor (TNF)-α using anti-cytokine antibody MACSPlex capture beads. Cytokine profiles of PBMCs showed significantly lower levels of GM-CSF, IFN-γ, IL-6, IL-9, IL-10, IL-17A, and TNF-α (p < 0.0001) in COVID-19 ICU patients. In contrast, COVID-19 ICU patients showed higher median levels of IL-2 (p < 0.001) and IL-5 (p < 0.01) by PBMCs. As for neutrophils, COVID-19 ICU patients showed significantly lower levels of GM-CSF, IFN-γ, IL-2, IL-4, IL-5, IL-6, IL-9, IL-10, IL-17A, IL-12, TNF-α (p < 0.0001), and IFN-α (p < 0.01). T-helper (Th)1:Th2 cytokine ratios revealed lower inflammatory cytokine for PBMCs and neutrophils in COVID-19 ICU patients. Cytokine production profiles and Th1:Th2 cytokine ratios suggest that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has an immunomodulatory effect on PBMCs and neutrophils. This study also suggests that the increased levels of several cytokines in the serum are not sourced from PBMCs and neutrophils.